INTEGRATION OF PEDAGOGICAL SOFTWARE TOOLS AND DATABASES IN AUTOMATION OF THE LEARNING PROCESS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This article analyzes the integration of pedagogical software tools and databases in the automation of the learning process. Based on learning methods and experiences, the effectiveness of integration and its impact on the learning environment are demonstrated.